Studi Kasus Pemanfaatan Tumbuhan Sebagai Obat-Obatan Tradisional Oleh Masyarakat Adat Kampung Naga Di Kabupaten Tasikmalaya - Nisa Nurmalasari; Sukarsa Sukarsa; Hexa Apriliana Hidayah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
A study entitled "A Case Study of Plant Utilization as Traditional Medicines by Indigenous Community of Kampung Naga" has been conducted from April-July 2010. The aims of the research to determine the type, how to used and to conserve plants used for medicine by the indegenous community in Kampung Naga. The research method was survey and the data collection was done with census method, interview and questionnaire for the tribe (kuncen), midwife (paraji), community leaders and residents of Kampung Naga.  The results of the research showed that there 108 plants species including to 50 families used as medicinal plants. The organ and nutritious plants used as medicine are the roots, rhizomes, tubers, stems, seeds, flowers, fruits, and leaves, or the whole plant parts. The way to use the medicinal plants includes boiing, just posted, and immediately eaten after steaming. The plants used as medicine were obtained from the gardens, forests, yards, roadside, moor and fields. The conservation efforts undertaken by the community of Kampung Naga consist of plant planting and cultural conservation.